Machu Picchu - Peterson, Sheryl (Mankato, Minn: Creative Education, 2005)
Describes the mysterious Inca city of Machu Picchu built high up in the Andes mountains.
Includes index.
Accelerated Reader
Keywords: Inca architecture -- Juvenile literature; Incas -- History -- Juvenile literature; Machu Picchu Site (Peru) -- Juvenile literature; Peru -- Antiquities -- Juvenile literature